METHOD FOR UPGRADING MATERIALS OBTAINED FROM END-OF-LIFE LITHIUM-ION BATTERIES - FAQIR, Hakim; LAMSAYETYI, Isam; BENZAKOUR, Intissar; OUZAOUIT, Khalid (2025)
The present invention relates to a method for selectively upgrading the elements in a material obtained from a mixture of end-of-life batteries. The invention relates more particularly to the field of upgrading the metal elements including cobalt, nickel and manganese present in the materials obtained from end-of-life lithium-ion batteries. The present invention also presents a solution for upgrading lithium and also graphitic carbon, in the form of lithium carbonates and graphitic carbon in the case where the material originates from rechargeable batteries. The method that is the subject of this invention thus makes it possible to upgrade the elements contained in a material obtained from end-of-life lithium-ion batteries so as to have new products that can be used for a second use for the preparation of active materials for lithium-ion batteries.